Judging faith, punishing sin : inquisitions and consistories in the early modern world - Parker, Charles H., 1958-; Starr-LeBeau, Gretchen D. (Cambridge University Press, 2017)
The first comparative analysis of Catholic inquisitions and Calvinist consistories in the great Christian age of reformation.